2006
DOI: 10.1017/s0950268806007308
|View full text |Cite
|
Sign up to set email alerts
|

Greek measles epidemic strain, 2005–2006

Abstract: The purpose of this work was the molecular study of the virus strain that caused the last measles outbreak in Greece. Twenty-four saliva specimens were obtained from selected patients serologically confirmed as measles cases between December 2005 and March 2006. Measles virus (MV) detection was performed by a nested RT-PCR. The 447-bp segment of the N gene of these MV strains was used for genotyping. The N gene sequences of the Greek MV strains were identical to each other, therefore a phylogenetic tree was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Most children who developed measles in our study were unvaccinated or partially vaccinated as also reported in previous measles epidemics in Greece [5,20]. These results are similar to results described in other European studies experienced large outbreaks at the same period [11,21,22].…”
Section: Plos Onesupporting
confidence: 91%
“…Most children who developed measles in our study were unvaccinated or partially vaccinated as also reported in previous measles epidemics in Greece [5,20]. These results are similar to results described in other European studies experienced large outbreaks at the same period [11,21,22].…”
Section: Plos Onesupporting
confidence: 91%
“…In Brazil the goal of interrupting the transmission of endemic measles virus (MV) by the end of 2000 using strategies developed by the Pan American Health Organization (PAHO), which included recommendations for vaccination activities, intended to achieve high population immunity together with sensitive surveillance for suspected measles cases, including effective virological and serological surveillance 1,2 . However this strategy was not implemented in many countries of worldwide and measles outbreaks continued occurring 3,4,5 .…”
Section: Introductionmentioning
confidence: 99%